2010
DOI: 10.1152/ajpheart.00565.2009
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell responses to atheroprone flow are driven by two separate flow components: low time-average shear stress and fluid flow reversal

Abstract: To simulate the effects of shear stress in regions of the vasculature prone to developing atherosclerosis, we subjected human umbilical vein endothelial cells to reversing shear stress to mimic the hemodynamic conditions at the wall of the carotid sinus, a site of complex, reversing blood flow and commonly observed atherosclerosis. We compared the effects of reversing shear stress (time-average: 1 dyn/cm(2), maximum: +11 dyn/cm(2), minimum: -11 dyn/cm(2), 1 Hz), arterial steady shear stress (15 dyn/cm(2)), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
88
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 34 publications
(49 reference statements)
8
88
0
Order By: Relevance
“…16,[20][21][22] Morphological changes represent a late response of endothelial cells on flow exposure. 23 The experiments performed confirmed typical morphological changes of human endothelial cells under the influence of atheroprotective shear stress 24 versus atheroprone 25 and static …”
Section: Discussionsupporting
confidence: 63%
“…16,[20][21][22] Morphological changes represent a late response of endothelial cells on flow exposure. 23 The experiments performed confirmed typical morphological changes of human endothelial cells under the influence of atheroprotective shear stress 24 versus atheroprone 25 and static …”
Section: Discussionsupporting
confidence: 63%
“…Similarly, we found that approximately 50% of the in vivo genes were also conserved, whereas approximately 50% were not when our in vivo data were compared with another independent study recently reported by Conway et al (supplemental Table 7). 14 These results demonstrate that approximately half of the mechanosensitive genes found in vivo can be confirmed in vitro, whereas the other half may not be found in vitro because of phenotypic changes in cultured cells. These findings clearly demonstrate the critical need of in vivo models in studying flow-dependent vascular responses and diseases.…”
Section: Discussionmentioning
confidence: 72%
“…In most studies, gene expression profiles in endothelial cells exposed to laminar shear were compared with that of static culture conditions, 9-17 whereas a few compared laminar shear with that of oscillatory or turbulent shear, 14,43,45 better simulating pathophysiologic conditions. These microarray studies have identified many mechanosensitive genes, such as Klf2, Klf4, BMP-4, cathepsins, and Angpt2, and subsequent studies have revealed functional significance of these mechanosensitive genes in regulation of inflammation, thrombosis, vascular remodeling, angiogenesis, and arteriogenesis, 11,[19][20][21][22][26][27][28][29][30] demonstrating the critical use of these microarray studies in studying vascular biology and diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…76 HUVECs exposed to high steady shear stress (15 dyn/cm 2 ) for 24 h aligned to the direction of flow, while cells exposed to low steady shear stress of 1 dyn/cm 2 or to the reversing flow were randomly oriented. Upon stopping the perfusion of THP-1 monocytes after 24 h, significant increase for adhesion was observed in the cells exposed to the reversing flow compared to static, low and high stress.…”
Section: Flow-based In Vitro Models and Cams Expressionmentioning
confidence: 99%